2002
DOI: 10.1007/bf02818787
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification ofStreptomyces sp. and assay of its exocellular water-soluble blue pigments

Abstract: A bacterial strain producing a great amount of blue pigment during submerse fermentation was isolated and identified. Based on morphological characteristics, cell-wall chemotype and sequence of 16S rRNA gene, the strain should belong to the genus Streptomyces; it had 99.4% homology of 16S rRNA gene sequence with that of Streptomyces indigocolor. The pigment production by the strain was affected by carbon and nitrogen sources. The main components of the pigment mixture (detected by HPLC and TLC) were tentativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The pXL100 plasmid from this strain was isolated using a modified version of a previously mentioned protocol . A. orientalis HCCB10007 and the plasmid‐free strain A. orientalis ATCC43490 were grown at 28 °C in Gause's synthetic agar medium , and the transformants and A. mediterranei were cultured in Bennet medium . For vancomycin production, spores of A. orientalis and its derivative were inoculated into a 250‐ml, baffled flask containing 25 ml of seed medium (20 g L −1 glycerol, 40 g L −1 amidulin, 20 g L −1 soybean flour, 15 g L −1 glucose, 6 g L −1 KNO 3 , 0.2 g L −1 KH 2 PO 4 , 0.4 g L −1 MgCl 2 .6H 2 O), cultivated at 28 °C and 220 rpm for 44 h and then transferred to production medium (20 g L −1 glycerol, 20 g L −1 soybean flour, 6 g L −1 KNO3, 0.2 g L −1 KH 2 PO 4 , 0.4 g L −1 MgCl 2 .6H 2 O, 3 g L −1 CaCO 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…The pXL100 plasmid from this strain was isolated using a modified version of a previously mentioned protocol . A. orientalis HCCB10007 and the plasmid‐free strain A. orientalis ATCC43490 were grown at 28 °C in Gause's synthetic agar medium , and the transformants and A. mediterranei were cultured in Bennet medium . For vancomycin production, spores of A. orientalis and its derivative were inoculated into a 250‐ml, baffled flask containing 25 ml of seed medium (20 g L −1 glycerol, 40 g L −1 amidulin, 20 g L −1 soybean flour, 15 g L −1 glucose, 6 g L −1 KNO 3 , 0.2 g L −1 KH 2 PO 4 , 0.4 g L −1 MgCl 2 .6H 2 O), cultivated at 28 °C and 220 rpm for 44 h and then transferred to production medium (20 g L −1 glycerol, 20 g L −1 soybean flour, 6 g L −1 KNO3, 0.2 g L −1 KH 2 PO 4 , 0.4 g L −1 MgCl 2 .6H 2 O, 3 g L −1 CaCO 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Among the types of chromatography used for pigment purification are flash chromatography [88], column chromatography on alumina [64], thin-layer chromatography (TLC) [46,55,59], ion-exchange chromatography [66], high-performance liquid chromatography (HPLC) [71,92], and preferentially coupled to mass spectroscopy (MS) [77,86,93]. Thus, between some of the columns used are SephadexG-50 [66,67], silica gel columns [61,85], Kromasil ODS C-18 columns [86], Sephadex LH-20 [87,91,103,104], Zorbax ODS C18 [97], Silica-coated glass plates [97], silica-gel-coated aluminum sheets [99], and DEAE-Sepharose columns [100]. In special cases, the compounds separated were detected by UV illuminator [74].…”
Section: Pigment Purificationmentioning
confidence: 99%
“…Even though one of the main disadvantages of pigments is their stability, only 17% of the selected articles evaluated them. The stability of the pigment includes assays under different conditions of pH, temperature, or light [76,97], or, in the presence of metal ions, additives, vitamins, and reducing and oxidizing agents [82,86].…”
Section: Stability Tests Of the Pigmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, blue pigments are divided into two certain kinds, natural and synthetic pigments. Although the synthetic pigments are mainly used as colorants in food or cosmetic industry, it is found that the synthetic colors are hardly nutrients, and some of them are toxic [1][2][3] to some extent. So the natural pigments, safer than synthetic ones, are being increasingly emphasized.…”
Section: Introductionmentioning
confidence: 99%